1992
DOI: 10.1177/101053959200600110
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Duration of Breastfeeding in a Rural Population of Saudi Arabia

Abstract: A study was conducted to demonstrate factors influencing duration of breastfeeding in Al-Jamoom Western region of Saudi Arabia. Information was obtained on 476 children under the age of three years and their mothers in nine of the villages in this area. A predesigned questionnaire was administered to the mothers to obtain information on age, education, fertility parameters and antenatal care during pregnancy with the index children. Multiple regression analysis was used to analyze the effect of different biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…The age range of infants included in the studies (and hence length of recall) varied across a wide range of ages. Four studies [18-20,29] asked mothers about feeding their infants in the last five years, four studies [21,23,24,27] included infants less than 2.5 years, and five studies investigated feeding practices in infants aged less than 12 months [30-34]. Three studies [22,26,28] included infants 6 months or younger, while one study included infants and children 0–9 years old [35].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The age range of infants included in the studies (and hence length of recall) varied across a wide range of ages. Four studies [18-20,29] asked mothers about feeding their infants in the last five years, four studies [21,23,24,27] included infants less than 2.5 years, and five studies investigated feeding practices in infants aged less than 12 months [30-34]. Three studies [22,26,28] included infants 6 months or younger, while one study included infants and children 0–9 years old [35].…”
Section: Resultsmentioning
confidence: 99%
“…However, those studies which used the WHO definition reported that the ‘exclusive breastfeeding’ rate at six months of age ranged from 1.7% [26] to 24.4% [28]. Other studies found low rates of ‘exclusive breastfeeding’ at six months after birth: 0.8% [19]; 8.9% [24] and 5.6% [35]. On the other hand, two national surveys recorded relatively high rates of ‘exclusive breastfeeding’ at six months of age of 33% and 38%, respectively [18,20].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations